TINGKAT PENERIMAAN MASYARAKAT TERHADAP PEMBANGUNAN JALAN DUA LAJUR DI KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Sintya Claudia; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in Pasir Penyu Regency, Indragiri Hulu district. The formulation of the problem referred to local people advantage and disadvantage. Besides, it also benefit to check the acceptance rate of local people. This research used society exchange theory that consisted of cost and reward. Meanwhile, the research design was quantitative descriptive. The population was the whole number of local people that dwelled in along of these two ways area. The total sample was sixty-four respondents which was obtained by census technique in that less than a hundred respondents. In order to collect the data, the researcher used interview, observation and documentation method that was supported by using questionnaire. Then, in order to obtain information and analyze result finding, researcher used quantitative descriptive analysis. The final result was concluded that local people could obtain more advantage such as increasing personal income, less of traffic congestion and reducing traffic accident. Furthermore, the drawback referred to a reduce of property land and building damage. Finally, the highest rate on the acceptance belong to those who had purposed this program since the days before. Keywords: Social Exchange, Society, Development